Assessment of nanofiltration efficiency for simultaneous concentration of copper and recovery of acid from highly acidic wastewater - Bencheng Hu; Haowen Wu; Wenhao Su; Keyu Yao; Li Long; Pengfei Sun; Yongcheng Wang; Lin Lin; Hao Guo; Xiao-yan Li (Water Research, 2026)

Multi-Year Predictability of Sandy Shoreline Change from Remote-Sensing Reconstruction and a Spatiotemporal Transformer - Keyu Tao; Fenzhen Su; Fengqin Yan; Vincent Lyne; Jiaojie Zhang (Journal of Marine Science and Engineering, 2026)
Most studies of sandy shoreline forecasting address relatively short time scales. Under limited annual observations and strong shoreline persistence, the added value of a Transformer over simple baselines and the influence of remotely sensed shoreline definitions remain insufficiently tested. Using Xichong Beach, Shenzhen, we constructed 40-year shoreline series for 80 transects from 284 quality-controlled Landsat waterlines acquired during 1986–2025. We compared a quality-controlled annual landward-envelope composite waterline with annual median waterlines and examined the effects of transect spacing and positional error on long-term change rates. We then developed a residual spatiotemporal Transformer that uses 10 years of shoreline states and historical wind–wave exposure to directly predict five future horizons, and compared it with persistence, rolling linear trend, and random forest models. The annual landward-envelope composite waterline was systematically landward of the annual median waterline (positional RMSE, 12.78 m), but their alongshore LRR patterns were strongly correlated (r = 0.982) and identified consistent major erosion–accretion zones. After Monte Carlo error propagation, the beach-mean LRR was −0.250 m yr−1 (95% interval, −0.299 to −0.203 m yr−1), whereas the direction of change remained uncertain at 39 local transects. Across 400 year–transect locations in the independent 2021–2025 evaluation period, the Transformer produced the lowest RMSE, MAE, and Dynamic RMSE (9.403, 7.399, and 12.042 m, respectively), with an RMSE skill of 27.0% relative to persistence. Environmental features yielded a small gain during rolling validation but no stable improvement in the independent evaluation period. SHAP attribution identified recent shoreline state as the dominant predictive information, followed by wind–wave exposure. Direct forecasts for 2026–2030 gave a beach-mean displacement of −8.527 m in 2030 (95% conditional residual bootstrap interval, −12.514 to −4.950 m), although every local-transect interval crossed zero. Multi-year predictability is therefore scale dependent: beach-mean trends are more resolvable, whereas local change directions remain constrained by observation error and model residuals.

Grazing-induced enhancement of rhizosphere effect on soil multifunctionality is linked to altered microbial life-history strategies in semiarid grasslands - Nuo Xu; Le Li; Yuhong Luo; Yunxiang Jin; Keyu Bai; Qiuli Bao; Jiahui Liu; Yufan Bao; Yuchun Yan (Agriculture, Ecosystems & Environment, 2026)

Biocontrol potential of Bacillus amyloliquefaciens LJ1 in enhancing disease resistance and quality preservation of Nanguo pears against Penicillium expansum - Zilong Li; Jiamin Jiang; Keyu Sun; Yan Ding; Shuhong Ye (Postharvest Biology and Technology, 2026)

Unraveling the drivers of corn yield response to optimization fertilization in plateau acidic red soils - Zhengfa Chen; Keyu Yan; Hui Yan; Xiaohan Mei; Chi Wang; Xingwei Chen; Wanli Hu; Bin Fu; Ming Ni; Zhiwu Li; Qingsong Duan; Yanmei Hu; et al. (Field Crops Research, 2026)

Fiber-regulated vibration suppression and mechanical behavior of CFRP corrugated channel cored sandwich structures - Jiaming Sun; Yanlong Xu; Keyu Zhu; Leilei Yan; Xitao Zheng; Zhichun Yang (Engineering Structures, 2025)

Metagenomic analysis of bacterial fitness and plasmids carrying blaTEM-1 and virulence genes before and after cleaning and disinfection in pig slaughterhouses - Shanshan Chu; Yan Chen; Zhuoqun Xu; Jie Zhou; Keyu Li; Qi Zhang; Min Qian; Jianzhong Han; Daofeng Qu (Journal of Hazardous Materials, 2025)

Dynamic quantitative characterization method for the weathering degree of earthen heritage sites surfaces based on 3D scanning technology and wavelet transform theory - Wenwu Chen; Qiang Qi; Keyu Wang; Shuai Zhang; Zhiqian Guo; Kebing Ren; Haitao Yan (Bulletin of Engineering Geology and the Environment, 2025)

Short-term emissions effect of rainfall erosion on soil CO2 in red soil sloped farmland in southern China - Keyu Yan; Xiaohan Mei; Chuan Zhang; Yanmei Hu; Daoxiang Wang; Zhengfa Chen; Xiaofeng Yang; Yanrui Shao; Yanjun Mao (Soil and Tillage Research, 2025)

Performance and mechanism of enhanced phosphorus release and volatile fatty acid production from Fe-P sludge via co-fermenting with agricultural wastes - Wei Yao; Rongrong Chang; Keyu Chen; Chaoxi Yang; Yan Lu; Shixu Wang; Kaiyue Dong; Baocheng Huang; Rencun Jin (Journal of Environmental Sciences, 2025)

p-chlorophenylalanine treatment accelerates tomato fruit ripening through hormone synthesis and glycolytic pathway during storage - Keyu Xu; Ran Yan; Hang Zhang; Lilai Yin; Wenbo Lei; Jianhui Cheng; Chen Huan; Yan Liu; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2025)

Activation of the Nrf2 Signaling Pathway by Tetrahydroberberine Suppresses Ferroptosis and Enhances Functional Recovery Following Spinal Cord Injury - Xiang Li; Heng Yu; Rongjie Liu; Jiansen Miao; Junlei Lv; Shu Yang; Yuxuan Zhu; Yan Chen; Keyu Lu; Chongan Huang; Xiangyang Wang (Molecular Neurobiology, 2025)

Impact of Proton Pump Inhibitors on Osimertinib-Induced Cardiotoxicity in NSCLC Patients - Haitao Wang; Sinan Ma; Weijia Huang; Keyu Chen; Jiao Xie; Na Wang; Youjia Li; Qianting Yang; Xin Yang; Yan Wang (Cardiovascular Toxicology, 2025)

Stability of China's terrestrial ecosystems carbon sink during 2000-2020 - Liang Shi; Honglin He; Li Zhang; Junbang Wang; Xiaoli Ren; Guirui Yu; Peng Hou; Jixi Gao; Bin Chen; Keyu Qin; Lili Feng; Shaoqiang Wang; et al. (Resources, Conservation and Recycling, 2025)

Spatiotemporal changes and management measure to enhance ecosystem services in the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Yadong Liu; Xuchun Yan; Xiaoying Fan; Avirmed Dashtseren; et al. (Environmental Development, 2024)

Crystal and micro-nano structure bidirectional regulation of iron oxalate for high-lithium storage and ultralong-cycling life via ultrasound assistance - Qing Zhao; Keyu Zhang; Geng Gao; Bo Jin; Guangping Zi; Rui Yan; Binbin Li; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Development of a CRISPR/Cas12a-based method to detect invasive aquatic species - Minlin Zhang; Xiaoling Zuo; Jiantao Liang; Keyu Lu; Liyun Wei; Xu Yan; Huihong Zhao; Songyong Gan; Jinhui Wu; Qing Wang (Aquaculture, 2024)

Increased ecological land and atmospheric CO2 dominate the growth of ecosystem carbon sinks under the regulation of environmental conditions in national key ecological function zones in China - Mengyu Zhang; Honglin He; Li Zhang; Guirui Yu; Xiaoli Ren; Yan Lv; Zhong'en Niu; Keyu Qin; Yanni Gao (Journal of Environmental Management, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Isolation of a facultative methanotroph Methylocystis iwaonis SD4 from rice rhizosphere and establishment of rapid genetic tools for it - Yinghui Wang; Yuying Wang; Keyu Zhou; Haili Zhang; Minggen Cheng; Baozhan Wang; Xin Yan (Biotechnology Letters, 2024)

Advancements in smart building envelopes: A comprehensive review - Guanqun Wang; Junjian Fang; Chengchu Yan; Dehai Huang; Kai Hu; Keyu Zhou (Energy and Buildings, 2024)

A stronger association of mental disorders with smaller particulate matter and a modifying effect of air temperature - Keyu Wu; Junwen Tao; Qiyue Wu; Hong Su; Cunrui Huang; Qingrong Xia; Cuizhen Zhu; Jing Wei; Min Yang; Junwei Yan; Jian Cheng (Environmental Pollution, 2024)

The relationship between repeated impacts and CAI strength of sandwich structure considering different impactor shape in individual impact - Keyu Zhu; Xitao Zheng; Jiaming Sun; Guoyue Wang; Leilei Yan (Engineering Structures, 2024)

Moderate grazing increased carbon, nitrogen and phosphorus storage in plants and soil in the Eurasian meadow steppe ecosystem - Miao Wang; Chu Zhang; Sisi Chen; Yu Zhang; Tianqi Yu; Xiaojuan Xue; Lianhai Wu; Wenneng Zhou; Xiangjun Yun; Ruirui Yan; Keyu Bai (Science of The Total Environment, 2024)

How does grazing pressure affect feed intake and behavior of livestock in a meadow steppe in northern China and their coupling relationship - Tianqi Yu; Ruirui Yan; Chu Zhang; Sisi Chen; Zhitao Zhang; LeiFeng Guo; Tianci Hu; Chengxiang Jiang; Miao Wang; Keyu Bai; Wenneng Zhou; Lianhai Wu (Science of The Total Environment, 2024)

Stochastic and deterministic assembly processes of bacterial communities in different soil aggregates - Yan Wang; Kun Zhu; Xin Chen; Keyu Wei; Rong Wu; Gang Wang (Applied Soil Ecology, 2024)

Extraction kinetics of separating molybdenum(Ⅵ) over iron(Ⅲ) from high acid leach solutions with mixtures of P507 and N235 - Miaomiao Peng; Keyu Shen; Yangjing Tan; Zhiyi Hu; Chun Liu; Zhixiong Liu; Wenbin Yan; Jun Hua; Fei Li (Minerals Engineering, 2023)

Proteomic profiling of purified avian leukosis virus subgroup J particles - Sheng Chen; Yiming Yan; Liguo Gao; Shuang Gao; Keyu Feng; Hongxin Li; Xinheng Zhang; Weiguo Chen; Feng Chen; Qingmei Xie (Veterinary Microbiology, 2023)

Spatiotemporal variations and driving factors for potential wind erosion on the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Xin Ma; Yadong Liu; Xuchun Yan; Xiaoying Fan; et al. (Science of The Total Environment, 2023)

Effects of xeric shrubs on soil microbial communities in a desert in northern China - Yanfei Sun; Yuqing Zhang; Wei Feng; Shugao Qin; Zhen Liu; Yuxuan Bai; Ru Yan; Keyu Fa (Plant and Soil, 2017)

Genetic manipulation of a transcription-regulating sequence of porcine reproductive and respiratory syndrome virus reveals key nucleotides determining its activity - Haihong Zheng; Keyu Zhang; Xing-Quan Zhu; Changlong Liu; Jiaqi Lu; Fei Gao; Yan Zhou; Hao Zheng; Tao Lin; Liwei Li; Guangzhi Tong; Zuzhang Wei; et al. (Archives of Virology, 2014)